They arrive with new information. Tourism flows and production efficiency in the European regions - Raffaele Paci; Emanuela Marrocu (European Regional Science Association (ERSA), 2010)
Firms productivity is crucially influenced by knowledge spillovers generated either by other firms located nearby or by direct contacts with consumers or by foreign demand in the case of traded products. In this paper we propose a new channel of efficiency-enhancing knowledge diffusion, which can be exploited by local firms to extract relevant information on consumer preferences: direct contacts with tourism flows. Tourists have the peculiar feature of being external consumers, who directly arrive to the destination region and this represents a remarkable advantage for the local enterprises, as the latter can exploit the new information and increase the overall efficiency level of the local economy. More specifically, we examine, within a spatial estimation framework, tourism flows as determinants of regional total factor productivity, controlling also for other intangible factors (such as human, social and technological capital) and for the degree of accessibility. We apply the analysis to a sample of 199 European regions belonging to the EU15 member countries, plus Switzerland and Norway. The empirical results show that tourism flows enhance regional efficiency and that a positive role is also played by intangible assets, infrastructures and spatial spillovers.
Keywords: L83; D83; O33; R10; 330; tourism; information; customer knowledge; total factor productivity; European regions